2021
DOI: 10.1002/adma.202105923
|View full text |Cite
|
Sign up to set email alerts
|

Wafer‐Scale Electroactive Nanoporous Silicon: Large and Fully Reversible Electrochemo‐Mechanical Actuation in Aqueous Electrolytes

Abstract: Porous silicon has been attracting much attention since the discovery of self-organized porosity in a monolithic semiconductor. [1][2][3][4][5][6][7] It provides a single-crystalline medium with anisotropic pores for the fundamental study of nanoconfinement on the structure and dynamics of matter. [7][8][9][10][11][12] Interface-dominated optical, electrical, and thermal properties attract the attention of the applied sciences in fields ranging from in vivo [4] and opto-electronics [13] via biosensing [6,14] t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Confinement of the matter in prose matrix delivers materials with new properties important for the application in nanotechnology and electronic industry. 61,62 The properties of those materials are averaged over the size distribution and quality of the pore assemble in the confining matrix. The experimental and theoretical investigation in a single gap can be considered as local (single pore) structure characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Confinement of the matter in prose matrix delivers materials with new properties important for the application in nanotechnology and electronic industry. 61,62 The properties of those materials are averaged over the size distribution and quality of the pore assemble in the confining matrix. The experimental and theoretical investigation in a single gap can be considered as local (single pore) structure characterization.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] Nanoporous Si as a nanostructured scaffold offers a wide range of applications for the exploration of the fundamentals of spatially confined condensed-matter systems. [25][26][27][28][29][30] As a nanoporous mainstream semiconductor np-Si is interesting for sensorics, actuorics, (bio-)photonics, and drug delivery [16,[31][32][33][34][35][36][37][38] as well as energy storage and conversion. [39][40][41][42][43] Filling the pore space with soft or hard materials, for example, electrically conductive polymers can improve properties such as electrical conductivity and mechanical robustness.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the extreme spatial confinement of np-Si, the pure spatial restriction and the interactions with the pore walls can hamper significantly hydrodynamic flow and self-diffusion, which results in slow process kinetics. [32,47,[49][50][51][52][53][54] One approach to address this challenge is the synthesis of hierarchically porous silicon (hp-Si). Pore diameters in the order of micrometers result in bulk-like flow properties and a low diffusion inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that migration of ions in mesoporous silicon was retarded due to high viscosity of water near hydrophilic surface and surface roughness. 25 From these literatures, a study on the dependence of surface charge density on pore diameter will be required to link the experimental and simulation studies and provide direct evidence on the effects of confinement on interfacial reactions.…”
Section: Introductionmentioning
confidence: 99%